HUBUNGAN PENERAPAN CORPORATE GOVERNANCE DAN SOCIAL CORPORATE TERHADAP MANAJEMEN PAJAK (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2015) - Dhanendra Ganang W; Imam Ghozali (Diponegoro Journal of Accounting, 2017)
This study aims to examine the effect of the number of boards of commissioners, the percentage of independent commissioners, the amount of compensation board of commissioners, audit committee, and Corporate Social Responsibility to corporate tax management. This study used multiple linear regression analysis using SPSS. The population used in this study consists of manufacturing companies listed in Indonesia Stock Exchange for the period 2012-2015. Samples were obtained in this study as many as 30 companies, bringing the total overall sample to be observed during the years 2012 to 2015 a total of 120. The results show that there is a significant positive effect on the number of commissioners tax management. There is a significant positive effect on the percentage of independent board tax management. There is a significant positive effect on the amount of compensation commissioners tax management. There is no influence of the audit committee of the tax management. There is no influence of Corporate Social Responsibility for the management of taxes. There is no effect of firm size on tax management. There is a significant positive effect on the profitability of tax management.